Long-Term Outcomes in Adult Patients With Pulmonary Hypertension After Percutaneous Closure of Atrial Septal Defects. (January 2022) - Akseer, Selai; Abrahamyan, Lusine; Lee, Douglas S.; Huszti, Ella; Meier, Lukas M.; Osten, Mark; Benson, Lee; Horlick, Eric
Abstract : Background: Pulmonary hypertension (PH), recently redefined as mean pulmonary arterial pressure >20 mm Hg (PH20 ), may be observed in patients with atrial septal defects (ASD). We aimed to determine the effect of preprocedural PH20 status on outcomes among patients undergoing ASD closure. Methods: Study population was selected from a retrospective registry of adult patients who underwent percutaneous ASD closure from 1998 to 2016 from a single center and had right heart catheterizations during the procedure. The clinical registry was linked to administrative databases to capture short- and long-term outcomes. Results: We included a total of 632 ASD closure patients of whom 359 (56.8%) had PH20 . The mean follow-up length was 7.6±4.6 years. Patients with PH20 were older (mean age 56.5 versus 43.1 years, P <0.001) and a higher prevalence of comorbidities including hypertension (54.3% versus 21.6%, P <0.001) and diabetes (18.1% versus 5.9%, P <0.001) than those without PH. In a Cox proportional hazards model after covariate adjustment, patients with PH had a significantly higher risk of developing major adverse cardiac and cerebrovascular events (heart failure, stroke, myocardial infarction, or cardiovascular mortality), with hazards ratio 2.45 (95% CI, 1.4–4.4). When applying the prior, mean pulmonary arterial pressure ≥25 mm Hg (PH25 ) cutoff, a significantly higher hazard of developing major adverse cardiac and cerebrovascular events was observed in PH versus non-PH patients. Conclusions: ASD patients with PH undergoing closure suffer from more comorbidities and worse long-term major adverse cardiac and cerebrovascular events outcomes, compared with patients without PH. The use of the new PH20 definition potentially dilutes the effect of this serious condition on outcomes in this population. Abstract : Supplemental Digital Content is available in the text.